2017
DOI: 10.1111/1471-0528.14744
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing ablation effects of a microbubble contrast agent on high‐intensity focused ultrasound: an experimental and clinical study

Abstract: Objective To investigate the relationship between SonoVue ablation enhancement effects on high-intensity focused ultrasound (HIFU) and the concentration of SonoVue and timing of HIFU.Design Two randomised controlled trials.Setting An animal centre in a university and a gynaecological department in a university hospital in China.Population or sample 63 rabbits and 143 patients with a solitary uterine fibroid.Methods Among the 63 rabbits, three were assigned to the control group. The other 60 were evenly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…As sacrococcygeal pain could be related to tissue injury due to the penetration of HIFU beyond the target region to the sacrococcygeal region, it can be concluded that the use of a lower total energy in the CEUS+HIFU group may reduce HIFU-induced tissue injury in the sacrococcygeal region. In agreement with results of the present study, Jiang et al [ 16 ] and Cheng et al [ 18 ] reported a significantly smaller EEF and a lower incidence of sacrococcygeal pain in SonoVue-based CEUS group compared with control group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As sacrococcygeal pain could be related to tissue injury due to the penetration of HIFU beyond the target region to the sacrococcygeal region, it can be concluded that the use of a lower total energy in the CEUS+HIFU group may reduce HIFU-induced tissue injury in the sacrococcygeal region. In agreement with results of the present study, Jiang et al [ 16 ] and Cheng et al [ 18 ] reported a significantly smaller EEF and a lower incidence of sacrococcygeal pain in SonoVue-based CEUS group compared with control group.…”
Section: Discussionsupporting
confidence: 93%
“…These effects of residual Sonazoid may enable HIFU to achieve the same level of ablation with a lower amount of energy. [ 18 , 19 , 47 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MBs with HIFU can enhance ablation effects. Bai [85] pretreated with SonoVue and introduced them into rabbits and patients with a solitary uterine fibroid. In the experimental study, the highest temperature and the largest necrotic volume in the liver were observed when HIFU sonication started at 60 seconds after administration of SonoVue.…”
Section: Hifu-involved Treatments Against Tumorsmentioning
confidence: 99%
“…The microbubbles, which the contrast agents are made of, can make acoustic changes of the tissues and make HIFU treatment more efficient. There are many studies that show the use of contrast-enhanced HIFU treatment has effects and proved that SonoVue is safety and can be used in treatment of uterine fibroids to enhance the ablation effects of HIFU [6]. Most of them were performed in Asia.…”
Section: Introductionmentioning
confidence: 99%